WHO NEEDS THE HISTORICAL SCIENCE AND FOR WHAT? - Vladislav F. Marukhin; Anatoliy I. Utkin (Высшее образование в России)
This paper is the review of the monograph of prof. V.B. Chistyakov "Historical component in higher education" (Moscow: Moscow State Industrial University Publ., 2015), which addresses the topical problems of teaching history in higher school.